2010
DOI: 10.1097/bsd.0b013e31819b08da
|View full text |Cite
|
Sign up to set email alerts
|

Aperius PercLID Stand Alone Interspinous System for the Treatment of Degenerative Lumbar Stenosis

Abstract: These results indicate that Aperius PercLID system offers an easy, safe, and effective treatment for patients with lumbar degenerative stenosis. Thus, this device system treatment represents a valid alternative to the traditional surgical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
(16 reference statements)
0
12
1
Order By: Relevance
“…Fracture rates, and the means of detecting fractures, vary between studies, making direct comparisons difficult. The rate of 7 % overall (including 2 % reported by the surgeons) in this study was less than has been reported in a similar study of other IPDs (29 %) [15], but is higher than in other studies where no central analysis of X-rays was undertaken [15,16].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Fracture rates, and the means of detecting fractures, vary between studies, making direct comparisons difficult. The rate of 7 % overall (including 2 % reported by the surgeons) in this study was less than has been reported in a similar study of other IPDs (29 %) [15], but is higher than in other studies where no central analysis of X-rays was undertaken [15,16].…”
Section: Discussioncontrasting
confidence: 77%
“…The incidence of device removal during this time was higher than in some other studies [14,15] but lower than in others [17,18]. In a recently published systematic review of the effectiveness of interspinous implant surgery in a total of 563 patients with NIC, 6 % of devices were found to have required replacement or reoperation [19].…”
Section: Discussionmentioning
confidence: 63%
“…limiting extension, thus preventing the subsequent worsening of spinal canal and foraminal stenosis) undergoing compression during extension of the lumbar spine. [13][14][15][16][17][18] At that moment, provided that the bone does not fail, the extension movement, no longer obtainable due to the presence of the interspinous spacer, is now obtained at the level of different elastic structures, particularly the anterior annulus and facets, which will move opposite of the normal direction, opening instead of closing. In such conditions, an increased load is transferred to the bony structures, with consequent risk of acute or chronic failure.…”
Section: Discussionmentioning
confidence: 99%
“…From June 2007 to March 2010, we performed, at a single center, interspinous spacer implantation (Aperius PercLID, Medtronic) 3,4,[8][9][10]13,14 in all eligible patients with INC and radiologic diagnosis of central canal and/or foraminal stenosis. All patients underwent an MR imaging or CT study of the lumbar spine preoperatively, to confirm stenosis of the central canal and/or foramina and to diagnose the most severely affected levels.…”
Section: Data Collection and Patientsmentioning
confidence: 99%
“…In both cases a microdiscectomy was performed, since foraminal stenosis by intraforaminal disc protrusion was persistent and it was considered to be the real cause of nerve dysfunction. The incidence of device removal during this time was low [4548]. In a recently published systematic review regarding effectiveness of interspinous implant surgery in a total of 563 patients with NIC, 6% of devices required replacement or reoperation [49].…”
Section: Discussionmentioning
confidence: 99%